Pengaruh Hair Mask dari Saripati Stroberi dan Minyak Kelapa Murni (Virgin Coconut Oil) untuk Perawatan Rambut Kering - Anisya Nur Qory ah; Tyas Asih Surya Mentari (Lembaga Yasin AlSys, 2026)
Dry hair is often experienced by female students who actively use high-temperature hair styling tools in beauty practice, causing the hair to become dull, brittle, and easily damaged due to the reduction of its natural moisture. One effort that can be made to address this condition is the use of a hair mask made from natural ingredients that is safe and environmentally friendly. This study aims to analyze the effect of a hair mask made from strawberry extract and virgin coconut oil (Virgin Coconut Oil/VCO) on the treatment of dry hair. This study employed an experimental method with a pretest-posttest design. The research subjects were female students of the Department of Makeup and Beauty, Faculty of Tourism and Hospitality, Universitas Negeri Padang, who had dry hair conditions. Data were collected using observation sheets and hair condition assessments, and were then analyzed using descriptive statistics and difference tests. The results showed that the use of a hair mask made from strawberry extract and virgin coconut oil (Virgin Coconut Oil/VCO) significantly improved dry hair condition, especially in the aspects of moisture, elasticity, and hair texture. These findings were supported by the results of the Wilcoxon Signed Rank Test, which showed a significance value of less than 0.05 for the three variables. Thus, there was a difference in hair condition before and after the treatment, indicating that the natural-ingredient hair mask was proven to have a positive effect on improving dry hair condition. This study confirms the potential use of natural ingredients as an effective and more environmentally friendly alternative for hair treatment.